Sejarah Perundang-Undangan Pendidikan Islam di Indonesia - Bashori Bashori (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: The long history of Islamic education in Indonesia can not be separated from the development of historicity policy from time to time. This paper will discuss specifically the development of Islamic education in Indonesia in the post-independence period that is from 1945 until the Soekarno (1959-1966), Soeharto (1966-1998), and government in the reformation era (1998-present). The long history of the nation and country can not be separated from the practical journey of Islamic education, which also experienced ups and downs, marked by important events as a milestone in formulating the policy of the role of Islamic education in the midst of society. Keywords: Undang-Undang, Pendidikan Islam